Elektronsko obvladovanje dokumentov za podporo sistema kakovosti po standardu ISO 9001 - Snoj, Pavel (Uporabna informatika (Ljubljana), 1999)
The article presents the importance of ISO 9001 standard in software supportedsolution which ensures that users can easily work with documents necessary for the company to operate according to the ISO 9001 standard. The purpose of ISO 9001 standard is to give users an assurance of a supplifier`s suitability, which means that the suplifier operates to the standard of the appropriate quality sistem. There are of course some problems to be overcome with the implementation of the quality sistem, the most crucial problem being that of document management. The solution we are offering has been designed to create an effective system for document management, supporting team work, providing a simple way of searching and sorting documents and ensuring an undisturbed workflow or documents - from their creation, to confirmation and archival.
Keywords: ISO 9001; kontrola kvalitete; računalniški program Lotus Notes